Fresh Versus Frozen Testicular Sperm Samples in Microdissection Testicular Sperm Extraction Intracytoplasmic Sperm Injection Treatment - Hatırnaz, Şafak; Başaranoğlu, Serdar; Hatırnaz, Ebru; Pektaş, Mine Kanat (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objective: The present study aims to compare the clinical outcomes of fresh versus frozen testicular samples in patients with non-obstructive azoospermia who would undergo intracytoplasmic sperm injection procedure. Study Design: This is a retrospective review of 541 patients with non-obstructive azoospermia who consecutively underwent microdissection testicular sperm injection and intracytoplasmic sperm injection between January 2010 and October 2014. Results: A total of 4896 mature oocytes were collected from the partners of azoospermic men and 1894 sperms were retrieved by microdissection testicular sperm procedures. About 1036 fresh sperms were used to perform intracytoplasmic sperm injection in 296 men with non-obstructive azoospermia whereas 858 in 245 azoospermic men. Approximately 1228 embryos were obtained after intracytoplasmic sperm injection and 1080 embryos were transferred. After embryo transfer, 146 clinical pregnancies occurred and 125 pregnancies ended up with live birth. The fertilization, implantation, clinical pregnancy and live birth rates were respectively 44.6%, 33.4%, 28.0% and 24.7% for 296 fresh microdissection testicular sperm cycles. On the other hand, the fertilization, implantation, clinical pregnancy and live birth rates were respectively 46.5%, 32.7%, 25.7% and 21.2% for 245 frozen microdissection testicular sperm cycles. There was no statistically significant difference between the fresh and frozen microdissection testicular sperm injection cycles in aspect of fertilization, implantation, clinical pregnancy and liver birth rates (p=0.125, p=0.194, p=0.196 and p=0.182). Conclusion: The utilization of fresh and frozen sperms in microdissection testicular sperm - intracytoplasmic sperm injection cycles has similar clinical outcomes. The use of frozen sperms obtained by testicular sperm can be considered as an efficient and safe approach for avoiding unnecessary ovarian hyperstimulation and repetitious interventions on testicular tissues.